APLICACIÓN DE UN SISTEMA CONTABLE BASADO EN LAS NORMAS INTERNACIONALES DE INFORMACIÓN FINANCIERA (NIIF) PARA LA COMPAÑÍA TELEVISIÓN SATELITAL ZAMORA CIA. LTDA. DE LA CIUDAD DE ZAMORA, EN EL PERÍODO ENERO A MARZO DEL 2014 - Paccha Murquincho, Martha Myriam (2016)
This thesis entitled "IMPLEMENTATION OF AN ACCOUNTING SYSTEM BASED ON INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) FOR SATELLITE ZAMORA COMPAÑÍATELEVISIÓN CIA. LTDA. CITY OF ZAMORA IN THE PERIOD FROM JANUARY TO MARCH 2014” itself which was developed by a suitable method, which provided the relevant information in relation to all aspects that required to give priority attention to the difficulties they showed, provide it with a theoretical-practical extension for the proper and full implementation, while providing compliance with the rule that dictates the Superintendence of Companies. In the course and development of the thesis, we can deduce that all the specific objectives proposed in the project work from the beginning to the end of it came true. The objectives were: The first focuses on follow procedures for the implementation of IFRS the Company Satellite Television Co. Zamora. Ltda.the same as was done through the lifting of the initial inventory, plan and manual accounts up to the financial statements. The second objective relates to recognize which group each of the accounts used in the financial statements, for which each account of the chart of accounts of the Company are analyzed, as we have we belong to Cash and cash equivalents; Furniture and Fixtures, Television Equipment, Computer Equipment, Vehicle belongs to Property, Plant and Equipment. 6 The third objective is to describe the changes they made to apply IFRS in the financial statements of the Company, which was able to compare the financial statements under NEC between the Financial Statements under IFRS, and see the new presentation of the accounts which were used therein during the accounting process. The methodology used to develop the thesis was based on the IFRS for Small and Medium Entities to apply in the accounting system of the company. I began with the knowledge of economic activity devoted, its name; continue with the lifting of inventory recognized accounts handled by the company and each time it was analyzed. The recording of transactions that allowed visualization not provisioned doubtful accounts, the tenth or the depreciation of property, plant and equipment, and finally the presentation of financial statements under IFRS was conducted. At the end of the thesis the most important findings is the difference between the presentation of financial statements under IFRS on NEC was determined; obtaining the application of IFRS, there is a profound change, but rather, a reference to accounting standards already known, and always used just looking for consistency and comparability in the presentation of results.